The impact of serial translocation bottlenecks on the genetic diversity of Anegada Rock Iguanas (Cyclura pinguis) in the British Virgin Islands - Giuliano Colosimo; Zachary Dykema; Mark E. Welch; Gad Perry; Zachary Harlow; Heidi Davis; Kelly A. Bradley; Gabriele Gentile; Glenn P. Gerber (Conservation Genetics, 2026)

Challenges and solutions to biodiversity conservation in arid lands - Yuanming Zhang; Akash Tariq; Alice C. Hughes; Deyuan Hong; Fuwen Wei; Hang Sun; Jordi Sardans; Josep Peñuelas; Gad Perry; Jianfang Qiao; Alishir Kurban; Xiaoxia Jia; et al. (Science of The Total Environment, 2023)

High infection rates of Toxoplasma gondii in cattle, sheep and pigs from Israel - Monica Leszkowicz Mazuz; Adi Weiss; Oren Beer; Sharon Tirosh-Levy; Irena Riklis; Zeev Dveyrin; Efrat Rorman; Naama Zaaroor Cohen; Michal Perry Markovich; Gad Baneth (Comparative Immunology, Microbiology and Infectious Diseases, 2023)

The next great migration: the story of movement on a changing planet - Gad Perry (Biological Invasions, 2020)

Archipelagic genetics in a widespread Caribbean anole - R. Graham Reynolds; Tanner R. Strickland; Jason J. Kolbe; Bryan G. Falk; Gad Perry; Liam J. Revell; Jonathan B. Losos (Journal of Biogeography, 2017)
Aim We examine the influence of fluctuating sea levels in a land‐bridge archipelago on the apportioning of intraspecific genetic diversity and divergence in the widespread Puerto Rican crested anole ( Anolis cristatellus ). We compare three alternative scenarios for genetic diversification in an archipelagic species that contrast the relative influences of periodic isolation versus island connectedness driven by fluctuating sea levels. Our approach combines information from geography and population genetics to assess the influence of island size, island isolation, island historical geography, and population genetic processes such as drift on the contemporary distribution of genetic variation within and among islands. Location The Puerto Rico Bank in the Caribbean focusing primarily on the Spanish, British and U.S. Virgin Islands. Methods We used nuclear and mitochondrial DNA sequences and microsatellite genotypes sampled from A. cristatellus populations to investigate: (1) the broad‐scale pattern of phylogeographical divergence across Puerto Rico Bank islands and (2) diversification within the Virgin Islands archipelago. For the first component, we used sequence data to reconstruct the relationships among 542 samples from across the species range. For the second component, we examined the relative influences of island size, isolation, and population genetic processes on the distribution of genetic diversity across the Virgin Islands. Results In the Virgin Islands, A. cristatellus is represented by a monophyletic clade except on the island of Vieques, where two divergent clades coexist. We found evidence for non‐equilibrium dynamics in the Virgin Islands, suggesting spatial population expansion during intraglacial periods of low sea level. Main conclusions We found limited evidence that periods of island isolation affected patterns of genetic diversity and differentiation. Instead, we found that the patterns of genetic diversity and divergence in A. cristatellus in the Virgin Islands archipelago are likely shaped by long‐term persistence in the region and periods of population spatial expansion.

Forecasting the Risk of Brown Tree Snake Dispersal from Guam: a Mixed Transport‐Establishment Model - GAD PERRY; DAN VICE (Conservation Biology, 2009)
The brown tree snake ( Boiga irregularis ) is a devastating invader that has ecologically and economically affected Guam and is poised to disperse further. Interdiction efforts are being conducted on Guam and some of the potential receiving sites, but no tools exist for evaluating the potential for snake incursion; thus, the amount of effort that should be invested in protecting particular sites is unknown. We devised a model that predicts the relative risk of establishment of the brown tree snake (BTS) at a given site. To calculate overall risk, we incorporated in the model information on the likelihood of an organism entering the transportation system, avoiding detection, surviving to arrive at another location, and establishing at the receiving end. On the basis of documented rates of snake arrival at receiving sites, the model produced realistic predictions of invasion risk. Model outputs can thus be used to prioritize interdiction efforts to focus on especially vulnerable receiving locations. We provide examples of the utility of the model in evaluating the impacts of changes in transportation parameters. Finally, the model can be used to evaluate the impacts that BTS establishment at an additional site and that creation of a new source of snakes would have. The use of qualitative inputs allows the model to be adapted by substituting data on other invasive species or transportation systems.

Animal Rights and Conservation - Gad Perry; Dan Perry (Conservation Biology, 2008)

Improving Interactions between Animal Rights Groups and Conservation Biologists - DAN PERRY; GAD PERRY (Conservation Biology, 2008)
Invasive species are often considered to be a major threat to biodiversity, leading conservation biologists to often recommend their complete eradication. Animal rights groups typically categorically oppose killing animals, and their opposition has brought eradication attempts of gray squirrels in northern Italy (Europe) and mute swans in Vermont to a halt. As a result native red squirrels may disappear from Europe and ecosystem‐wide impacts are expected to be caused by the swan. In contrast, cooperation between managers and animal rights groups has resulted in a successful control program for feral pigs in Fort Worth, Texas (U.S.A.). The philosophical differences between animal rights and conservation biologists' views make cooperation seem unlikely, yet documented cases of cooperation have been beneficial for both groups. We recommend that managers dealing with invasive species should consult with social scientists and ethicists to gain a better understanding of the implications of some of their policy decisions. In addition, we recommend that animal rights groups do more to support alternatives to lethal control, which are often excluded by economic limitations. Prevention of arrival of invasive species via application of the precautionary principle may be an especially productive avenue for such collaboration because it fits the goals and values of both groups.